Logistika za prometne inženirje - Letnik, Tomislav (University of Maribor Press, 2024)
Logistrics for Traffic and Transportation Engineers. The introduction of the textbook is dedicated to the basic concepts necessary for understanding the field of logistics and the current logistical challenges. The rest of the textbook presents the main components of the logistics system, its functions and the importance of logistics for the functioning of society. Particular attention is given to logistics in business processes related to procurement, production, sales, and after-sales as well as aspects of reverse logistics. The aspects of managing logistics processes are described and explained, with a particular focus on supply chains and urban logistics. The last part of the textbook is dedicated to the future development of logistics, with a detailed description of the processes of the physical Internet. Questions are posed at the end of each chapter to stimulate critical thinking and encourage students to explore the field of logistics beyond the boundaries of this textbook.